A randomized phase III study evaluating the efficacy of single-dose NEPA, a fixed antiemetic combination of netupitant and palonosetron, versus an aprepitant regimen for prevention of chemotherapy-induced nausea and vomiting (CINV) in patients receiving highly emetogenic chemotherapy (HEC). (28th October 2017) - Zhang, L; Lu, S; Feng, J; Dechaphunkul, A; Chang, J; Wang, D; Chessari, S; Lanzarotti, C; Jordan, K; Aapro, M
Abstract: Background: Co-administration of multiple antiemetics that inhibit several molecular pathways involved in emesis is required to optimize chemotherapy-induced nausea and vomiting (CINV) control in patients receiving highly emetogenic chemotherapy (HEC). NEPA, a fixed combination of a highly selective NK1 receptor antagonist, netupitant (300 mg), and the pharmacologically distinct 5-HT3 RA, palonosetron (PALO 0.50 mg), has shown superior CINV prevention compared with PALO in cisplatin and anthracycline/cyclophosphamide-based settings. This study is the first head-to-head comparison of NEPA versus an aprepitant (APR)/granisetron (GRAN) regimen. Patients and methods: This randomized, double-blind phase III study conducted in Asia was designed with the primary objective to demonstrate non-inferiority of a single oral dose of NEPA compared with a 3-day oral APR/GRAN regimen in chemotherapy-naïve patients receiving cisplatin-based HEC. All patients also received oral dexamethasone (DEX) on days 1–4. The primary efficacy endpoint was complete response (CR: no emesis/no rescue medication) during the overall (0–120 h) phase. Non-inferiority was defined as a lower 95% CI greater than the non-inferiority margin set at − 10%. Secondary efficacy endpoints included no emesis, no rescue medication, and no significant nausea (NSN). Results: Treatment groups were comparable for the 828 patients analyzed: predominantly male (71%); mean age 54.5 years; ECOG 0–1 (98%); lung cancer (58%). NEPA demonstrated non-inferiority to APR/GRAN for overall CR [NEPA 73.8% versus APR/GRAN 72.4%, 95% CI (−4.5%, 7.5%)]. No emesis [NEPA 75.0% versus APR/GRAN 74.0%, 95% CI (−4.8%, 6.9%)] and NSN rates [NEPA 75.7% versus APR/GRAN 70.4%, 95% CI (−0.6%, 11.4%)] were similar between groups, but significantly more NEPA patients did not take rescue medication [NEPA 96.6% versus APR/GRAN 93.5%, 95% CI (0.2%, 6.1%)]. NEPA was well tolerated with a similar safety profile to APR/GRAN. Conclusions: In this first study comparing NK1 RA regimens and DEX, NEPA administered only on day 1 was non-inferior to a 3-day oral APR/GRAN regimen in preventing CINV associated with HEC.